The Great Recession and unpaid work time in the United States: Does poverty matter? - Tamar Khitarishvili; Kijong Kim (Levy Economics Institute of Bard College, 2014)
In times of economic crises, household production, and the unpaid work time associated with it, can serve as a coping mechanism for absorbing the impact of shocks. Evidence from the Great Recession has been supportive of this possibility, and has revealed the presence of gender asymmetries stemming from men having experienced disproportionately high job losses. In this paper, we further examine the presence of poverty-based asymmetries in the unpaid work time changes of men and women given that the role of household production as a coping mechanism may vary by poverty status. We use the 2003-12 American Time Use Survey and conduct the Oaxaca Blinder decompositions of the changes in the unpaid work time along the business cycle. Our findings reveal that the changes in men's and women's unpaid work time indeed varied by poverty status. In particular, the reduction in women's unpaid work time was driven by nonpoor women. Among men, the lack of the change masked the increase in poor men's unpaid work time and the decrease in nonpoor men's unpaid work time. The decomposition results indicate that, in addition to the shifts in own employment status, shifts in spousal employment status also played a considerable role in explaining the gender differences in unpaid work time changes. In turn, varied shifts in the household structure were important drivers of the poverty-based differences in the unpaid work time changes. Furthermore, the forces underlying the changes in unpaid work time were not limited to the shifts in individual and household characteristics, as the portion of the unpaid work time changes unexplained by these characteristics remained sizable. This finding supports the hypothesis of poverty-based variation in unpaid work time adjustments in that, even without shifts in characteristics, poor and nonpoor individuals appeared to have responded to the recession in different ways.
Keywords: J22; D13; I32; J16; 330; Time Use; Household Production; Poverty; Gender; Great Recession